2014
DOI: 10.1177/1947603514534681
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Repair With Autologous Bone Marrow Mesenchymal Stem Cell Transplantation

Abstract: Clinical trials of various procedures, including bone marrow stimulation, mosaicplasty, and autologous chondrocyte implantation, have been explored to treat articular cartilage defects. However, all of them have some demerits. We focused on autologous culture-expanded bone marrow mesenchymal stem cells (BMSC), which can proliferate without losing their capacity for differentiation. First, we transplanted BMSC into the defective articular cartilage of rabbit and succeeded in regenerating osteochondral tissue. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19] Studies have shown success with combining arthroscopic marrow stimulation and postoperative intra-articular injections of stem cells in combination with hyaluronic acid (HA). 14,[19][20][21][22][23][24][25] We have previously published our clinical results involving a case series and a randomized controlled trial after arthroscopic subchondral drilling in combination with postoperative intra-articular injections of peripheral blood stem cells (PBSCs) and HA.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] Studies have shown success with combining arthroscopic marrow stimulation and postoperative intra-articular injections of stem cells in combination with hyaluronic acid (HA). 14,[19][20][21][22][23][24][25] We have previously published our clinical results involving a case series and a randomized controlled trial after arthroscopic subchondral drilling in combination with postoperative intra-articular injections of peripheral blood stem cells (PBSCs) and HA.…”
mentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are able to differentiate into chondrocytes and have been used to study chondrogenesis in vitro. Tissue engineering solutions to cartilage repair include autologous chondrocyte implantation, cartilage autografts and injection of MSCs into the damaged site [16,17]. However, these methods are not widely used and complications can arise from their application.…”
Section: Introductionmentioning
confidence: 99%
“…The transforming growth factor-β (TGF-β) signal pathway has been studied as a key regulator in the self-renewal, maintenance and differentiation of stem cells. [10][11][12] It has been reported that TGF-β1 plays an important role in cartilage development and is an important chondrogenic factor. 12,13 Moreover, some studies have demonstrated that cajanine has anti-tumor and anti-oxidant functions.…”
Section: Introductionmentioning
confidence: 99%